The Correlation between Iraqi EFL University Students' Self- regulation, Metacognitive Knowledge, and Writing Skill - Dehham, Sabeeha Hamza; Abbas, Salam Hamid (Journal of Posthumanism, 2025)
The current study looks at how Iraqi EFL university students' writing skills, metacognitive knowledge, and ability to self-regulate are related. In order to achieve this goal, 350 students from various Iraqi universities and colleges with an English department were selected at random during the 2022–2023 school year to participate in the current study. Three tools were sent to the participants: a writing skill assessment tool, a self-regulation tool, and a metacognitive knowledge questionnaire. We decided to use an essay test to evaluate your writing skills. The study found that Iraqi university students studying English as a foreign language have a moderate amount of self-regulation and a decent degree of metacognitive understanding. Additionally, there was a substantial correlation between the two variables. Consequently, EFL students' writing performance is great when they possess good levels of Metacognitive Knowledge and self-regulation.